Sobrac North online event: acoustics and architecture, ideas in practice: The first step of progress! - Rodrigues, Paulo Chagas (Acústica e Vibrações, 2022)
<span data-sheets-root="1" data-sheets-value="{"1":2,"2":"The virtual meeting, organized by Sobrac’s Northern Region, represented a remarkable initiative to promote and expand the dialogue on the critical role of acoustics in the field of architecture and urbanism. This event was particularly focused on the peculiarities and needs of the northern region of Brazil. The meeting was enriched by the participation of distinguished professionals and industry representatives, who brought their valuable practical experience in acoustic projects, significantly contributing to the depth and relevance of the discussions. The purpose of this forum was not only to exchange knowledge but also to raise awareness of the strategic importance of acoustics in urban development and construction projects in the region."}" data-sheets-userformat="{"2":15357,"3":{"1":0},"5":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"6":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"7":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"8":{"1":[{"1":2,"2":0,"5":{"1":2,"2":0}},{"1":0,"2":0,"3":3},{"1":1,"2":0,"4":1}]},"9":0,"10":1,"11":4,"12":0,"14":{"1":2,"2":0},"15":"Calibri","16":12}">The virtual meeting, organized by Sobrac’s Northern Region, represented a remarkable initiative to promote and expand the dialogue on the critical role of acoustics in the field of architecture and urbanism. This event was particularly focused on the peculiarities and needs of the northern region of Brazil. The meeting was enriched by the participation of distinguished professionals and industry representatives, who brought their valuable practical experience in acoustic projects, significantly contributing to the depth and relevance of the discussions. The purpose of this forum was not only to exchange knowledge but also to raise awareness of the strategic importance of acoustics in urban development and construction projects in the region.